Nonaqueous electrolyte electricity storage element and electricity storage device

By forming a dense carbon coating on the positive electrode active material of the nonaqueous electrolyte power storage element, the problem of the degradation of the output performance of lithium transition metal compounds after the charge and discharge cycle is solved, and the improvement of the output maintenance rate and the improvement of the initial output performance is achieved.

CN119866549APending Publication Date: 2025-04-22GS YUASA INT LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065885.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-15
Filing Date
2023-08-30
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The non-aqueous electrolyte power storage element using lithium transition metal compounds having polyanionic structures such as lithium iron phosphate as the positive electrode active substance, and the output performance is easily degraded after the charge and discharge cycle.

Method used

A positive electrode active material with a carbon coating layer is used, which contains carbon elements, and the density of the coating layer is controlled by an appropriate specific surface area ratio (0.40 to 0.80), thereby inhibiting the contact between the positive electrode active material and the non-aqueous electrolyte, and reducing the dissolution of transition metal cations and the formation of the film.

Benefits of technology

It effectively suppresses the decrease in the output maintenance rate after the charge and discharge cycle, and improves the initial output performance of the nonaqueous electrolyte power storage element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866549A_ABST
    Figure CN119866549A_ABST
Patent Text Reader

Abstract

A non-aqueous electrolyte electricity storage element according to one aspect of the present invention is provided with a positive electrode having a carbon-coated positive electrode active material having a positive electrode active material and a coating layer, a negative electrode having a negative electrode active material, and a non-aqueous electrolyte. The positive electrode active material contains a lithium transition metal compound having a polyanion structure, the coating layer contains a carbon element and covers at least a part of the positive electrode active material, and the ratio of the BET specific surface area of the positive electrode active material to the BET specific surface area of the carbon-coated positive electrode active material is 0.40-0.80. The negative electrode active material contains a carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and an electricity storage device. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. The above-mentioned non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are configured to charge and discharge by transferring charge transport ions between the two electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and double electric layer capacitors have also been widely popularized.

[0003] As an example of a non-aqueous electrolyte storage element, Patent Document 1 describes a lithium secondary battery using lithium iron phosphate as a positive electrode active material.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-215977 Summary of the invention

[0007] A non-aqueous electrolyte storage element using a lithium transition metal compound having a polyanion structure such as lithium iron phosphate as a positive electrode active material may suffer from a decrease in output performance after charge and discharge cycles.

[0008] The present invention has been made based on the above circumstances, and an object of the present invention is to provide a non-aqueous electrolyte electricity storage element and an electricity storage device capable of suppressing a decrease in the output retention rate after charge and discharge cycles.

[0009] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises: a positive electrode having a carbon-coated positive electrode active material, a negative electrode having a negative electrode active material, and a nonaqueous electrolyte, wherein the carbon-coated positive electrode active material comprises a positive electrode active material and a coating layer, the positive electrode active material comprises a lithium transition metal compound having a polyanion structure, the coating layer comprises a carbon element and covers at least a portion of the positive electrode active material, the ratio of the BET specific surface area of ​​the positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material is 0.40 to 0.80, and the negative electrode active material comprises a carbon material.

[0010] A power storage device according to another aspect of the present invention includes one or more power storage elements according to another aspect of the present invention, and includes two or more power storage elements.

[0011] A nonaqueous electrolyte electricity storage element and an electricity storage device according to one aspect of the present invention can suppress a decrease in the output retention rate after charge and discharge cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.

[0013] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION

[0014] First, the outline of the nonaqueous electrolyte electricity storage element and electricity storage device disclosed in this specification will be described.

[0015] [1] A non-aqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode having a carbon-coated positive electrode active material, a negative electrode having a negative electrode active material, and a non-aqueous electrolyte, wherein the carbon-coated positive electrode active material comprises a positive electrode active material and a coating layer, the positive electrode active material comprises a lithium transition metal compound having a polyanion structure, the coating layer comprises a carbon element and covers at least a portion of the positive electrode active material, the ratio of the BET specific surface area of ​​the positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material is 0.40 to 0.80, and the negative electrode active material comprises a carbon material.

[0016] The non-aqueous electrolyte storage element described in [1] above can suppress the decrease in the output maintenance rate after the charge and discharge cycle. The reason is still uncertain, but it is speculated to be the following reason. The positive electrode of the non-aqueous electrolyte storage element described in [1] above has a positive electrode active material containing a lithium transition metal compound (lithium iron phosphate, etc.) having a polyanion structure. In such existing non-aqueous electrolyte storage elements, the transition metal cations constituting the lithium transition metal compound are easily dissolved into the non-aqueous electrolyte, and a film derived from the above transition metal cations is sometimes formed on the surface of the negative electrode active material by repeated charge and discharge cycles. That is, due to the formation of this film, the output performance is sometimes reduced after the charge and discharge cycle. Among them, when the negative electrode active material is composed of metallic lithium, the metallic lithium is dissolved and precipitated by the charge and discharge reaction, so the process of forming the film derived from the above transition metal cations on the surface of the negative electrode active material due to repeated charge and discharge cycles is slow, and the effect of this film on the output performance is very small. On the other hand, when the negative electrode active material contains a carbon material, the carbon material will not be dissolved and precipitated due to the charge and discharge reaction, so the formation of the film from the above-mentioned transition metal cations on the surface of the negative electrode active material due to repeated charge and discharge cycles is significantly advanced, and the film has a great influence on the output performance. In contrast, the positive electrode of the non-aqueous electrolyte storage element described in [1] above has a carbon-coated positive electrode active material in which the above-mentioned positive electrode active material is coated with a coating layer containing carbon elements. Therefore, the contact between the above-mentioned positive electrode active material and the non-aqueous electrolyte can be suppressed. In addition, the ratio of the BET specific surface area of ​​the above-mentioned positive electrode active material to the BET specific surface area of ​​the above-mentioned carbon-coated positive electrode active material is within a certain range. Among them, the ratio of the BET specific surface area of ​​the above-mentioned positive electrode active material to the BET specific surface area of ​​the above-mentioned carbon-coated positive electrode active material represents the degree of density of the above-mentioned coating layer. That is, in the carbon-coated positive electrode active material involved in the present invention, the above-mentioned positive electrode active material is coated with the above-mentioned coating layer that is appropriately dense. Therefore, even when the negative electrode active material contains a carbon material, the coating layer can effectively suppress the dissolution of the transition metal cations and the formation of the film on the surface of the negative electrode active material, thereby suppressing the decrease in the output retention rate after charge and discharge cycles.

[0017] [2] In the non-aqueous electrolyte storage element described in [1] above, the negative electrode active material may contain graphite, and the average particle size of the negative electrode active material may be less than 20 μm. Generally, the output performance of the non-aqueous electrolyte storage element can be improved by using a negative electrode active material with a small particle size, especially graphite with a small particle size. In this case, in the existing non-aqueous electrolyte storage element, if a lithium transition metal compound having a polyanion structure is used as the positive electrode active material, the formation of the above-mentioned film on the surface of the negative electrode active material may be accelerated. On the other hand, for the non-aqueous electrolyte storage element described in [2] above, as described above, the dissolution of the above-mentioned transition metal cations can be suppressed by using the above-mentioned coating layer that coats the above-mentioned positive electrode active material. Therefore, by making the above-mentioned negative electrode active material contain graphite and making the average particle size of the above-mentioned negative electrode active material less than the above-mentioned upper limit, the effect of the present invention of suppressing the decrease in the output maintenance rate after the charge and discharge cycle while improving the initial output can be significantly exerted.

[0018] [3] In the non-aqueous electrolyte storage element described in [1] or [2] above, the above ratio may be greater than 0.50, and the average particle size of the above negative electrode active material may be less than 5 μm. By making the average particle size of the above negative electrode active material less than the above upper limit, the initial output can be further improved. In addition, by making the above ratio greater than the above lower limit, the decrease in the output maintenance rate after the charge and discharge cycle can be more reliably suppressed. Therefore, by making the above ratio greater than the above lower limit and making the average particle size of the above negative electrode active material less than the above upper limit, the initial output can be further improved while suppressing the decrease in the output maintenance rate after the charge and discharge cycle.

[0019] In the present invention, the "average particle size" refers to the particle size distribution measured by the laser diffraction and scattering method according to JIS-Z-8825 (2013) on a dilution obtained by diluting the sample to be measured with a solvent, and the particle size (median particle size) at which the volume-based cumulative distribution calculated according to JIS-Z-8819-2 (2001) reaches 50%. In addition, in the present invention, the "BET specific surface area" is calculated as follows: the sample to be measured is immersed in liquid nitrogen, nitrogen molecules are physically adsorbed on the surface of the particles by supplying nitrogen, and the pressure and adsorption amount at this time are measured. As a specific measurement method, the nitrogen adsorption amount [m 2 The obtained nitrogen adsorption amount was divided by the mass [g] of the sample to obtain a value which was taken as the BET specific surface area [m 2 / g].

[0020] It should be noted that in the determination of the above-mentioned average particle size and BET specific surface area, the sample collected from the non-aqueous electrolyte storage element after the initial charge and discharge is used as the measurement object. Specifically, the sample of the measurement object is collected by the following steps. First, the non-aqueous electrolyte storage element after the initial charge and discharge is discharged at a constant current of 0.1C to the discharge termination voltage during normal use, and becomes a discharged state. Here, normal use refers to the situation where the non-aqueous electrolyte storage element is used under the charge and discharge conditions recommended or specified by the non-aqueous electrolyte storage element. Next, the non-aqueous electrolyte storage element in the discharged state is disassembled, the positive electrode or the negative electrode is taken out, and the components (electrolyte, etc.) attached to the positive electrode or the negative electrode are fully cleaned with dimethyl carbonate. Thereafter, the positive electrode or the negative electrode is dried under reduced pressure at room temperature for 24 hours. Next, the powder of the positive electrode active material layer or the negative electrode active material layer is collected from the positive electrode or the negative electrode. Any components such as the conductive agent mixed in the powder of the positive electrode active material layer or the negative electrode active material layer are removed by wind classification, and the sample of the measurement object is collected. The non-aqueous electrolyte storage element is disassembled and the sample to be measured is collected in an argon atmosphere with a dew point of -60°C or less.

[0021] The "BET specific surface area of ​​the carbon-coated positive electrode active material" and the "BET specific surface area of ​​the positive electrode active material" are obtained by the following steps. Initially, the positive electrode taken out by disassembling the non-aqueous electrolyte storage element is washed and dried as described above, and the BET specific surface area of ​​the collected carbon-coated positive electrode active material is measured. Next, the above-mentioned coating layer is removed by calcining the above-mentioned carbon-coated positive electrode active material at 350°C in an atmospheric atmosphere for 4 hours. Thereafter, the BET specific surface area of ​​the positive electrode active material from which the above-mentioned coating layer has been removed is measured.

[0022] [4] Another aspect of the present invention relates to a power storage device comprising one or more nonaqueous electrolyte power storage elements as described in any one of [1] to [3] above, and comprising two or more nonaqueous electrolyte power storage elements. The power storage device described in [4] above can suppress a decrease in the output retention rate after a charge and discharge cycle because it comprises one or more nonaqueous electrolyte power storage elements as described in any one of [1] to [3] above.

[0023] The following is a detailed description of a non-aqueous electrolyte storage element, a storage device, a method for manufacturing a non-aqueous electrolyte storage element, and other embodiments of the present invention. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.

[0024] [Non-aqueous electrolyte storage element]

[0025] A nonaqueous electrolyte storage element (hereinafter also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, a nonaqueous electrolyte, and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator between them, or a wound type in which a positive electrode and a negative electrode are wound with a separator between them. The nonaqueous electrolyte exists in a state contained in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter also referred to as "secondary battery") is described.

[0026] <Positive electrode>

[0027] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0028] The positive electrode substrate has electrical conductivity. Whether it has "electrical conductivity" is determined by measuring the volume resistivity of 10 -2 Ω·cm is used as the threshold value for judgment. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity and cost. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, as the positive electrode substrate, aluminum foil or aluminum alloy foil is preferred. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.

[0029] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be improved, and the energy density per unit volume of the non-aqueous electrolyte storage element can be improved.

[0030] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by including a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, includes a binder and a conductive agent.

[0031] (Positive Electrode Active Material Layer)

[0032] In one embodiment of the present invention, the positive electrode active material layer includes a carbon-coated positive electrode active material. In addition, the positive electrode active material layer may include any component such as a conductive agent, a binder (adhesive), a thickener, and a filler as needed.

[0033] The carbon-coated positive electrode active material has a positive electrode active material and a coating layer (hereinafter also referred to as "carbon coating layer") that contains carbon elements and covers at least a portion of the positive electrode active material. The above-mentioned carbon-coated positive electrode active material is usually a granular material with particles of the positive electrode active material as the core. As a method for manufacturing the carbon-coated positive electrode active material, for example, a positive electrode active material, an organic compound that serves as a carbon source, and a solvent are mixed to obtain a mixture, and the mixture is crushed with a bead mill to prepare a slurry, followed by drying and heat treatment. As the above-mentioned organic compound, polyvinyl alcohol, polyvinyl pyrrolidone, cellulose, starch, gelatin, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, polystyrene sulfonic acid, polyacrylamide, polyvinyl acetate, glucose, fructose, galactose, mannose, maltose, sucrose, lactose, glycogen, pectin, alginic acid, glucomannan, chitin, hyaluronic acid, chondroitin, agarose, polyether, polyol, etc. can be cited. Examples of the polyol include polyethylene glycol, polypropylene glycol, polyglycerol, and glycerin.

[0034] The positive electrode active material of the carbon-coated positive electrode active material contains a lithium transition metal compound having a polyanion structure.

[0035] Examples of the lithium transition metal compound (hereinafter also referred to as a "polyanion compound") include LiFePO4, LiMnPO4, LiNiPO4, LiMn 0.5 Ni 0.5 PO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2FePO4F, Li2CoPO4F, Li2NiPO4F, etc. Among these, phosphate ions (PO4 3- ) compound (phosphate compound), more preferably lithium iron phosphate (LiFePO4). The polyanion compound can be a compound in which a part of the constituent atoms or polyanions is replaced by other atoms or other anion species. In general, the conductivity of the polyanion compound is low, but the conductivity can be improved by coating at least a part with a carbon coating layer. The polyanion compound can be used alone or in combination of two or more.

[0036] The content of the lithium transition metal compound in the positive electrode active material of the carbon-coated positive electrode active material may be, for example, 95 mass % to 100 mass %. That is, the positive electrode active material of the carbon-coated positive electrode active material may be substantially composed of only the lithium transition metal compound.

[0037] The content of the lithium transition metal compound in the carbon-coated positive electrode active material is preferably 90.0 mass % to 99.5 mass %, more preferably 92.0 mass % to 99.2 mass %, and further preferably 94.0 mass % to 99.0 mass %. By making the content of the lithium transition metal compound within the above range, the carbon-coated positive electrode active material can be easily manufactured.

[0038] In one embodiment of the present invention, the carbon-coated layer of the carbon-coated positive electrode active material contains carbon as described above. The content of carbon in the carbon-coated layer can be, for example, 95% by mass to 100% by mass. That is, the carbon-coated layer of the carbon-coated positive electrode active material can be substantially composed of only carbon. The carbon in the carbon-coated layer formed by the above steps usually exists in the form of a mixture of high crystalline carbon and low crystalline carbon.

[0039] As the lower limit of the content of the above-mentioned carbon element in the carbon-coated positive electrode active material, it is preferably 0.5 mass %, more preferably 0.7 mass %, and further preferably 1.0 mass %.On the other hand, as the upper limit of this content, it is preferably 3.0 mass %, more preferably 2.5 mass %, and further preferably 2.0 mass %.By making the content of the above-mentioned carbon element be above the above-mentioned lower limit, it is possible to utilize the carbon coating layer to fully coat the positive electrode active material, and it is possible to improve the output maintenance rate of the nonaqueous electrolyte storage element, etc. In addition, by making the content of the above-mentioned carbon element be below the above-mentioned upper limit, it is possible to relatively improve the content of the positive electrode active material, and improve the energy density of the nonaqueous electrolyte storage element.

[0040] The lower limit of the ratio of the BET specific surface area of ​​the positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material is 0.40, preferably 0.50, and more preferably 0.60. On the other hand, the upper limit of the above ratio is 0.80, preferably 0.77, and more preferably 0.75. Here, the ratio of the BET specific surface area of ​​the positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material indicates the degree of density of the carbon coating layer. If the above ratio is large, the BET specific surface area of ​​the carbon-coated positive electrode active material is small, which means that the carbon-coated positive electrode active material has a denser carbon coating layer. If the above ratio is small, the BET specific surface area of ​​the carbon-coated positive electrode active material is large, which means that the carbon-coated positive electrode active material has a coarser carbon coating layer. Therefore, if the above ratio is above the above lower limit, the above-mentioned positive electrode active material is coated with a suitably dense carbon coating layer, so it is easy to suppress the decrease in the output retention rate after the charge and discharge cycle. Furthermore, when the ratio is equal to or less than the upper limit, it is easy to ensure the ion conductivity of the positive electrode active material layer and to make the charge and discharge reaction uniform.

[0041] The lower limit of the BET specific surface area of ​​the carbon-coated positive electrode active material is preferably 10.0 m 2 / g, more preferably 13.0m 2 / g, more preferably 13.5m 2 On the other hand, the upper limit of the BET specific surface area of ​​the carbon-coated positive electrode active material is preferably 15.0 m 2 / g, more preferably 14.0m 2 / g, more preferably 13.8m 2 / g. If the BET specific surface area of ​​the above-mentioned carbon-coated positive electrode active material is above the above-mentioned lower limit, it is easy to improve the output performance. In addition, if the BET specific surface area of ​​the above-mentioned carbon-coated positive electrode active material is below the above-mentioned upper limit, it is easy to suppress the decrease in the output maintenance rate after the charge and discharge cycle. It should be noted that the BET specific surface area of ​​the carbon-coated positive electrode active material can be controlled by adjusting the BET specific surface area of ​​the positive electrode active material in the above-mentioned carbon-coated positive electrode active material and the BET specific surface area of ​​the carbon coating layer by the method described later.

[0042] The lower limit of the BET specific surface area of ​​the positive electrode active material in the carbon-coated positive electrode active material is preferably 4.0 m 2 / g, more preferably 5.0m 2 / g, more preferably 5.5m 2 On the other hand, the upper limit of the BET specific surface area of ​​the positive electrode active material is preferably 13 m 2 / g, more preferably 12m 2 / g, more preferably 11m 2 / g. If the BET specific surface area of ​​the positive electrode active material is above the lower limit, it is easy to improve the output performance. In addition, if the BET specific surface area of ​​the positive electrode active material is below the upper limit, it is easy to suppress the decrease in the output maintenance rate after the charge and discharge cycle. It should be noted that the BET specific surface area of ​​the positive electrode active material can be controlled by, for example, adjusting the time for pulverization with a bead mill in the above-mentioned method for producing the carbon-coated positive electrode active material.

[0043] The lower limit of the difference in BET specific surface area between the carbon-coated positive electrode active material and the positive electrode active material (the value obtained by subtracting the BET specific surface area of ​​the positive electrode active material from the BET specific surface area of ​​the carbon-coated positive electrode active material) is preferably 1.0 m 2 / g, more preferably 2.0m 2 / g, more preferably 2.5m 2 On the other hand, the upper limit of the difference is preferably 9.0 m / g. 2 / g, more preferably 8.0m 2 / g, more preferably 7.0m 2 / g. If the above difference is above the above lower limit, it is easy to improve the output performance. In addition, if the above difference is below the above upper limit, it is easy to suppress the decrease in the output maintenance rate after the charge and discharge cycle. It should be noted that the above difference is proportional to the BET specific surface area of ​​the carbon coating layer in the carbon-coated positive electrode active material. The BET specific surface area of ​​the carbon coating layer can be controlled, for example, by changing the carbon source or adjusting the heat treatment temperature and heat treatment time in the above-mentioned method for manufacturing the carbon-coated positive electrode active material.

[0044] The positive electrode active material layer may contain positive electrode active materials other than the carbon-coated positive electrode active materials. Examples of the other positive electrode active materials include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanionic compounds without a carbon coating layer, chalcogen compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ)O4, etc. As polyanionic compounds without a carbon coating layer, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be mentioned. As chalcogen compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be mentioned. Atoms or part of polyanions in these materials can be replaced by atoms or anionic species composed of other elements. The surfaces of these materials can be coated with other materials except the carbon coating layer. In the positive electrode active material layer, one of these materials can be used alone, or two or more of them can be mixed and used.

[0045] The carbon-coated positive electrode active material and other positive electrode active materials are particles (powders). The average particle size of the carbon-coated positive electrode active material is preferably, for example, 0.1 μm to 20 μm. By making the average particle size of the carbon-coated positive electrode active material greater than the above lower limit, it is easy to manufacture or operate the carbon-coated positive electrode active material. By making the average particle size of the carbon-coated positive electrode active material less than the above upper limit, the ion conductivity in the positive electrode active material layer is improved.

[0046] In order to obtain a powder with a predetermined particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, a method using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill, or a sieve can be cited. During pulverization, wet pulverization in which a non-aqueous solvent such as water or hexane coexists can also be used. As a classification method, a sieve, a wind classifier, etc. can be used as needed for both dry and wet methods.

[0047] The content of the carbon-coated positive electrode active material in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 96% by mass. By making the content of the carbon-coated positive electrode active material within the above range, the effects of the present invention such as improving the output maintenance rate after charge and discharge cycles can be significantly exerted.

[0048] The total content of all positive electrode active materials in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, further preferably 80% to 96% by mass, and further preferably 90% to 95% by mass. By making the total content of all positive electrode active materials within the above range, high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0049] The conductive agent is not particularly limited as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be cited. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be cited. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be cited. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be cited. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be cited. As the shape of the conductive agent, powder, fiber, etc. can be cited. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can be composited and used. For example, a material composited with carbon black and CNT can be used. Among these, from the viewpoint of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.

[0050] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. By making the content of the conductive agent within the above range, the energy density of the nonaqueous electrolyte storage element can be increased. It should be noted that the conductive agent does not include the above-mentioned carbon coating layer.

[0051] As the binder, for example, there can be mentioned thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0052] The content of the binder in the positive electrode active material layer is preferably 1% to 10% by mass, more preferably 2% to 9% by mass, and further preferably 3% to 6% by mass. By setting the content of the binder to the above range, the positive electrode active material can be stably maintained.

[0053] As thickeners, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be cited. When the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. In one embodiment of the present invention, it is sometimes preferred that the positive electrode active material layer does not contain a thickener.

[0054] The filler is not particularly limited. As fillers, inorganic oxides such as polyolefins such as polypropylene and polyethylene, silica, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other materials from mineral resources or their man-made products, etc., can be cited. In one embodiment of the present invention, it is sometimes preferred that the positive electrode active material layer does not contain a filler.

[0055] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0056] <Negative electrode>

[0057] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified for the positive electrode described above.

[0058] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or their alloys, carbonaceous materials, etc. can be used. Among these, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the perspective of cost, foil is preferred. Therefore, as the negative electrode substrate, copper foil or copper alloy foil is preferred. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.

[0059] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate to the above range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the secondary battery can be increased.

[0060] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains any component such as a conductive agent, a binder, a thickener, and a filler as needed. The conductive agent, the binder, the thickener, the filler, and any component can be selected from the materials exemplified for the positive electrode.

[0061] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0062] The negative electrode active material contains a carbon material. As the negative electrode active material, it can be appropriately selected from known carbon materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. As the negative electrode active material, for example, carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon) can be cited. Among these materials, graphite and non-graphite carbon are preferred, and graphite is more preferred. In the negative electrode active material layer, one of these materials can be used alone, or two or more of them can be mixed and used.

[0063] “Graphite” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge or discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.

[0064] “Non-graphite carbon” refers to the average lattice spacing (d ) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include non-graphitizable carbon and easily graphitizable carbon. Examples of non-graphite carbon include materials derived from resins, petroleum asphalt or materials derived from petroleum asphalt, petroleum coke or materials derived from petroleum coke, materials derived from plants, materials derived from alcohols, and the like.

[0065] Here, the "discharge state" refers to a state in which the lithium ions that can be absorbed and released accompanying the charge and discharge are fully released from the carbon material as the negative electrode active material. For example, the following state: in a monopolar battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is 0.7V or more.

[0066] "Non-graphitizable carbon" refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.

[0067] "Graphitizable carbon" refers to the above-mentioned 002A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.

[0068] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm to 100 μm, or 0.5 μm to 100 μm. By making the average particle size of the negative electrode active material above the above lower limit, it is easy to manufacture or handle the negative electrode active material. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. As a pulverizing method, for example, methods using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotary airflow jet mill or a sieve can be cited. Wet pulverization in which a non-aqueous solvent such as water or hexane coexists can also be used during pulverization. As a classification method, both dry and wet methods can use sieves, wind classifiers, etc. as needed.

[0069] The negative electrode active material is preferably a particle. In addition, as the upper limit of the average particle size of the negative electrode active material, it is preferably 20μm, more preferably 16μm, and further preferably 12μm. If the upper limit of the above average particle size is below the above upper limit, the effect of the present invention of easily improving the initial output and suppressing the decrease in the output maintenance rate after the charge and discharge cycle can be significantly exerted. In addition, from the same point of view, it is preferred that the negative electrode active material contains graphite, and the above average particle size is 20μm or less, more preferably contains graphite, and the above average particle size is 16μm or less, further preferably contains graphite, and the above average particle size is 12μm or less, and further preferably contains graphite, and the above average particle size is 5μm or less. On the other hand, as the lower limit of the average particle size of the negative electrode active material, from the perspective of manufacturing cost, it can be, for example, 0.5μm.

[0070] When the average particle size of the negative electrode active material is small, the transition metal cations from the positive electrode active material that are dissolved into the non-aqueous electrolyte sometimes accelerate the formation of the film on the surface of the negative electrode active material. That is, when the average particle size of the negative electrode active material is small, in order to cope with this, it is preferred to protect the positive electrode active material with the above-mentioned carbon coating layer that is appropriately dense. Therefore, from the perspective of both improving the initial output and suppressing the decrease in the output maintenance rate after the charge and discharge cycle, it is preferred that the ratio of the BET specific surface area of ​​the above-mentioned positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material is 0.50 to 0.80, and the average particle size of the negative electrode active material is 0.5 μm to 5 μm.

[0071] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99% by mass, and more preferably 90% to 98% by mass. By making the content of the negative electrode active material within the above range, it is possible to take into account both the high energy density and the manufacturability of the negative electrode active material layer. When the negative electrode active material is metallic Li, the content of the negative electrode active material in the negative electrode active material layer can be 99% by mass or more, or 100% by mass.

[0072] <Isolator>

[0073] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and a binder formed on one or both sides of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, porous resin films are preferred from the viewpoint of strength, and non-woven fabrics are preferred from the viewpoint of liquid retention of non-aqueous electrolytes. As the material of the substrate layer of the separator, from the viewpoint of insulation function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, for example, polyimides, aromatic polyamides, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can be used.

[0074] The heat-resistant particles contained in the heat-resistant layer preferably have a mass reduction of 5% or less when the temperature is raised from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably have a mass reduction of 5% or less when the temperature is raised from room temperature to 800°C. As materials whose mass reduction is less than the prescribed value, inorganic compounds can be cited. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as organosilicon and diamond; talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products. As inorganic compounds, monomers or composites of these substances can be used alone, or two or more can be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the nonaqueous electrolyte storage element.

[0075] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and refers to a value measured using a mercury porosimeter.

[0076] As a separator, a polymer gel composed of a polymer and an electrolyte can be used. As the polymer, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. If a polymer gel is used, it has the effect of suppressing leakage. As a separator, a porous resin film or non-woven fabric as described above can be used together with a polymer gel.

[0077] <Non-aqueous electrolyte>

[0078] As the non-aqueous electrolyte, a non-aqueous electrolyte solution can be used. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0079] As nonaqueous solvent, can suitably select from known nonaqueous solvent.As nonaqueous solvent, can enumerate cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc.As nonaqueous solvent, can use the solvent after the part of the hydrogen atom that comprises in these compounds is replaced by halogen.

[0080] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among them, EC is preferred.

[0081] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among them, EMC is preferred.

[0082] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, and more preferably a cyclic carbonate and a chain carbonate are used in combination. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted to improve the ion conductivity of the non-aqueous electrolyte. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be suppressed to a low level. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is preferably in the range of 5:95 to 50:50, for example.

[0083] As the electrolyte salt, it can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.

[0084] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3 can be cited. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0085] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.

[0086] In addition to the non-aqueous solvent and the electrolyte salt, the non-aqueous electrolyte may also contain additives. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,5- Halogenated anisole compounds such as difluoroanisole; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiapentane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, thioanisole, diphenyl disulfide, bipyridine disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, tetrakis(trimethylsilyl)titanate, monofluorolithium phosphate, difluorolithium phosphate, etc. These additives may be used alone or in combination of two or more.

[0087] Relative to the mass of the entire nonaqueous electrolyte, the content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, further preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By making the content of the additive within the above range, the capacity retention performance or charge-discharge cycle performance after high temperature storage can be improved, or the safety can be further improved.

[0088] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, button batteries, and the like.

[0089] Figure 11 shows a non-aqueous electrolyte storage element 1 as an example of a square battery. It should be noted that this figure is a perspective view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator clamped therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.

[0090] [Configuration of Power Storage Device]

[0091] The non-aqueous electrolyte storage element of the present embodiment can be used as a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements and can be mounted on a power supply for vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), a power supply for electronic devices such as personal computers and communication terminals, or a power supply for power storage, etc. In this case, the technology of the present invention can be applied to at least one non-aqueous electrolyte storage element contained in the storage unit.

[0092] An electric storage device according to one embodiment of the present invention includes at least one nonaqueous electrolyte storage element according to one embodiment of the present invention, and includes at least two nonaqueous electrolyte storage elements (hereinafter referred to as the "second embodiment"). The technology according to one embodiment of the present invention can be applied to at least one nonaqueous electrolyte storage element included in the electric storage device according to the second embodiment. The electric storage device may include one nonaqueous electrolyte storage element according to one embodiment of the present invention and one or more nonaqueous electrolyte storage elements unrelated to the one embodiment of the present invention, or may include two or more nonaqueous electrolyte storage elements according to one embodiment of the present invention.

[0093] Figure 2 2 shows an example of a power storage device 30 according to the second embodiment, which is formed by further combining power storage units 20 formed by combining two or more electrically connected non-aqueous electrolyte power storage elements 1. The power storage device 30 may include a bus bar (not shown) that electrically connects the two or more non-aqueous electrolyte power storage elements 1, a bus bar (not shown) that electrically connects the two or more power storage units 20, and the like. The power storage unit 20 or the power storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more non-aqueous electrolyte power storage elements.

[0094] [Method for producing a non-aqueous electrolyte storage device]

[0095] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and accommodating the electrode body and the non-aqueous electrolyte in a container. Preparing the electrode body includes: preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or winding the positive electrode and the negative electrode through a separator.

[0096] The method of accommodating the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution can be injected from an injection port formed in the container and then the injection port can be sealed.

[0097] [Other Embodiments]

[0098] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be applied within the scope of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and in addition, a part of the structure of a certain embodiment can be replaced by the structure of other embodiments or known technology. In addition, a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.

[0099] In the above embodiment, the case where the nonaqueous electrolyte storage element is used as a nonaqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) that can be charged and discharged is described, but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors, or lithium ion capacitors.

[0100] In the above embodiment, the positive electrode and the negative electrode are stacked with a separator, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other with a non-conductive layer formed on the active material layer of the positive electrode or the negative electrode.

[0101] Example

[0102] The present invention will be described in more detail below by way of examples. However, the present invention is not limited to the following examples.

[0103] [Example 1]

[0104] (Production of positive electrode)

[0105] First, a carbon-coated positive electrode active material was prepared according to the following steps.

[0106] Lithium hydroxide monohydrate, diammonium hydrogen phosphate, and ferrous sulfate heptahydrate are measured in a manner that the molar ratio of Li:Fe:P becomes 3:1:1, and mixed in ion exchange water to prepare a solution. Next, the solution is transferred to a polytetrafluoroethylene container and placed in a pressure-resistant hydrothermal reaction container. After the reaction container is fully replaced with nitrogen and sealed, it is heated at 170°C for 15 hours for hydrothermal synthesis. After the reaction is completed, the product obtained by naturally cooling to room temperature is fully washed with ion exchange water, and then dried under reduced pressure at 120°C for 6 hours, thereby obtaining a positive electrode active material of lithium iron phosphate. Thereafter, in order to form a carbon coating layer covering the positive electrode active material, the above-mentioned positive electrode active material powder and polyvinyl alcohol as a carbon source are mixed in ion exchange water, and a bead mill is used to treat zirconium oxide beads with a diameter of 0.1 mm, and wet pulverization is implemented. It should be noted that the mixing ratio of the positive electrode active material powder and polyvinyl alcohol is adjusted in such a way that the content of the carbon coating layer (carbon element) in the carbon-coated positive electrode active material becomes 1.0 mass%. The mixture was spray-dried using a spray dryer to obtain a granulated dry powder. Finally, the dry powder was heated at 720° C. for 2 hours in a tubular furnace under nitrogen flow to obtain a carbon-coated positive electrode active material.

[0107] The BET specific surface area B1 of the carbon-coated positive electrode active material and the BET specific surface area B2 of the positive electrode active material were 13.5 [m 2 / g] and 10.8[m 2 / g]. In addition, the ratio B2 / B1 of the BET specific surface area B2 of the above-mentioned carbon coating layer to the BET specific surface area B1 of the above-mentioned carbon-coated positive electrode active material (hereinafter also referred to as "active material BET ratio") is 0.80. It should be noted that, according to the viewpoints of the inventors, there is no substantial difference between the BET specific surface area measured before the initial charge and discharge described later and the BET specific surface area measured after the initial charge and discharge, and therefore, the measured value of the BET specific surface area measured before the initial charge and discharge is adopted in this embodiment. Here, "no substantial difference" means that the difference in the measured values ​​is less than 1%, and the same applies hereinafter.

[0108] Next, N-methylpyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode mixture paste containing the carbon-coated positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder at a mass ratio of 90:5:5 in terms of solid content. The positive electrode mixture paste was directly applied to both sides of the aluminum foil as the positive electrode substrate, and pressed after drying. Thus, a positive electrode with a positive electrode active material layer stacked on both sides of the positive electrode substrate was obtained.

[0109] (Production of negative electrode)

[0110] As a negative electrode active material, graphite particles with an average particle size of 12 μm are prepared. A negative electrode mixture paste is prepared using the above-mentioned graphite particles, styrene-butadiene rubber (SBR) as a binder, carboxymethyl cellulose (CMC) as a thickener, and water as a dispersion medium. It should be noted that the mass ratio of graphite particles, SBR and CMC is 98:1:1 (solid content conversion). The negative electrode mixture paste is applied to both sides of a copper foil as a negative electrode substrate and dried. Thereafter, roller pressing is performed to obtain a negative electrode. It should be noted that, according to the views of the inventors, there is no substantial difference between the average particle size of the negative electrode active material measured before the initial charge and discharge described later and the average particle size measured after the initial charge and discharge. Therefore, the measured value of the average particle size measured before the initial charge and discharge is adopted in this embodiment.

[0111] (Preparation of non-aqueous electrolyte)

[0112] LiPF6 as electrolyte salt was added at 0.9 mol / dm 3 The concentration of 200 μg / mL was dissolved in a non-aqueous solvent mixed at a volume ratio of EC:EMC of 30:70 to prepare a solution. The solution was obtained as a non-aqueous electrolyte.

[0113] (Fabrication of non-aqueous electrolyte storage element)

[0114] A wound electrode body was obtained using the positive electrode, the negative electrode and a polyolefin porous resin film as a separator. The electrode body was housed in a container, and a nonaqueous electrolyte was injected and sealed to obtain the nonaqueous electrolyte storage element of Example 1.

[0115] [Examples 2 to 16 and Comparative Examples 1 to 3]

[0116] For Examples 2 to 16 and Comparative Examples 1 to 3, a nonaqueous electrolyte storage element was obtained by the same procedure as in Example 1 except that the BET specific surface area B1 of the carbon-coated positive electrode active material, the BET specific surface area B2 of the positive electrode active material, the BET ratio of the active material, and the average particle size of the negative electrode active material were as shown in Table 1. It should be noted that the BET specific surface area B1 of the carbon-coated positive electrode active material, the BET specific surface area B2 of the positive electrode active material, and the average particle size of the negative electrode were adjusted by the following method.

[0117] The BET specific surface area of ​​the positive electrode active material was adjusted by changing the time of the bead mill treatment in the preparation of the carbon-coated positive electrode active material.

[0118] The BET specific surface area of ​​the carbon-coated positive electrode active material can be adjusted by adjusting the BET specific surface area of ​​the positive electrode active material described above and by changing the heating temperature in the final step of preparing the carbon-coated positive electrode active material.

[0119] The average particle size of the negative electrode active material was adjusted using a pulverizer.

[0120] [evaluate]

[0121] (1) Initial output

[0122] Each non-aqueous electrolyte storage element obtained was initially charged and discharged at 25°C according to the following method. After constant current charging at a current of 0.2C to 3.5V, constant voltage charging was performed at a voltage of 3.5V. The end condition of charging was that the charging current reached 0.01C. Thereafter, a 10-minute pause time was set. Thereafter, constant current discharge was performed at a current of 0.2C to 2.0V.

[0123] Next, constant current charging was performed at 25°C with a current of 1.0C to make the SOC 50%. Next, discharge was performed at a current of 0.2C, 0.5C or 1.0C for 30 seconds. After each discharge, constant current charging was performed at a current of 1.0C to make the SOC 50%. The relationship between the current in each discharge and the voltage at the 10th second after the start of the discharge was plotted, and the DC resistance was calculated from the slope of the straight line obtained from the plot of the three points. The output 10 seconds after the start of the discharge was calculated from the obtained DC resistance as the initial output. The results are shown in Table 1.

[0124] (2) Charge and discharge cycle test

[0125] Next, each nonaqueous electrolyte storage element was stored in a thermostatic chamber at 60° C. for 4 hours, and then charged to 3.5 V at a constant current of 1.0 C, and then discharged to 2.0 V at a constant current of 1.0 C. A rest time of 10 minutes was set after charging and discharging. This charge and discharge was repeated for 300 cycles.

[0126] (3) Output after charge and discharge cycle test

[0127] Thereafter, the output after the charge-discharge cycle test was obtained by the same procedure as that for obtaining the initial output. The percentage of the output after the charge-discharge cycle test relative to the initial output was obtained for each nonaqueous electrolyte storage element as the output maintenance rate. The results are shown in Table 1.

[0128] [Table 1]

[0129]

[0130] As shown in Table 1, the output maintenance rates of Examples 1 to 16 in which the active material BET ratio was 0.40 to 0.80 were 75% or more. On the other hand, the output maintenance rates of Comparative Example 1 in which the active material BET ratio was greater than 0.80 and Comparative Examples 2 and 3 in which the active material BET ratio was less than 0.40 were less than 75%. That is, it is believed that in Examples 1 to 16, by protecting the positive electrode active material with an appropriately dense carbon coating layer, the dissolution of iron ions from the positive electrode active material and the formation of a film from iron ions on the surface of the negative electrode active material can be suppressed.

[0131] Referring to Examples 1 to 16, the smaller the average particle size of the negative electrode active material, the larger the initial output. In addition, when the average particle size of the negative electrode active material is 5 μm, the initial output is significantly improved. That is, it is shown that even when the average particle size of the negative electrode active material is small, by properly controlling the BET ratio of the active material, it is possible to achieve both the improvement of the initial output and the suppression of the decrease in the output maintenance rate after the charge and discharge cycle.

[0132] Industrial Applicability

[0133] The present invention is applicable to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.

[0134] Explanation of symbols

[0135] 1 Non-aqueous electrolyte storage element

[0136] 2 Electrode body

[0137] 3 Container

[0138] 4 Positive terminal

[0139] 41 Positive lead

[0140] 5 Negative terminal

[0141] 51 Negative lead

[0142] 20 Storage unit

[0143] 30 Power storage device

Claims

1. A non-aqueous electrolyte storage element comprising: a positive electrode having a carbon-coated positive electrode active material, a negative electrode having a negative electrode active material, and a non-aqueous electrolyte, The carbon-coated positive electrode active material comprises a positive electrode active material and a coating layer, wherein the positive electrode active material contains a lithium transition metal compound having a polyanion structure, and the coating layer contains a carbon element and covers at least a portion of the positive electrode active material. The ratio of the BET specific surface area of ​​the positive electrode active material to the BET specific surface area of ​​the carbon-coated positive electrode active material is 0.40 to 0.80, The negative electrode active material contains a carbon material.

2. The nonaqueous electrolyte storage element according to claim 1, wherein The negative electrode active material contains graphite, and the average particle size of the negative electrode active material is 20 μm or less.

3. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The ratio is 0.50 or more, and the average particle size of the negative electrode active material is 5 μm or less. 4 . A power storage device comprising one or more nonaqueous electrolyte power storage elements according to claim 1 or 2 and comprising two or more nonaqueous electrolyte power storage elements.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2015215977A